Islamic Law and Imperialism: Tracing on The Development of Islamic Law In Indonesia and Malaysia - Imam Mawardi (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2018)
This study has demonstrated that the Dutch and British occupation in Indonesia and Malaysia, proves Edward Said’s assessment of imperialism a vehicle for cultural hegemony. In terms of the law, the Dutch influence on the development of legal system in Indonesia cannot be denied. Likewise, British imperialism also impacted the legal systems of Malaysia in a profound sense. Dutch colonialism, which lasted for approximately 350 years in Indonesia, left its mark on the region by introducing Roman law to the Islamic Judiciary, as did the 160 years of British colonialism in Malaysia, witnessed in the forced application of Common law. From political perspective, the changes wrought to the legal system and to Indonesian Islam are the consequence of Dutch political policies which claimed to be “modernizing” Indonesia. The pervasive influence and legacy of Dutch rule on the Indonesian legal system is the practice of codification. Many developments overtaking Indonesian. Islamic law is a manifestation of this practice. Efforts to unify and create uniformity with respect to the source of law, have resulted in the enactment the law of Marriage no. 1/1974, the law of the Religious Judiciary no. 7/1989, and Kompilasi Hukum Islam di Indonesia (Compilation of Islamic Law in Indonesia) among others. However, it is naïve to view such recent developments as mere products of the influence of Dutch rule. Sociologically, developments in other realms such as education, economy, social and political structures should also be taken into account when considering the development of Islamic law.